CHILDREN'S DRAMA ASSISTANCE AT THE BULAVA ARTS STUDY IN SINDUE - I Gusti Ketut Alit Saputra; Yunidar Yunidar; Nirmayanti Nirmayanti (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
Learning drama in literature at school is enough to provide an aesthetic and imaginative experience. Elementary school students need to be known to form mental attitudes and self-confidence. Assistance is expected to improve their ability to play drama. Mentoring is carried out for the children of the Bulava Art Studio. The goal is children's knowledge about theater and children's ability to play drama. The mentoring drama was carried out in three stages, 1) observing the activities of the Bulava Art Studio; 2) implementation of service activities; 3). They were writing devotional articles. The methods used are observation, lectures, physical exercise, giving examples, question and answer, discussions, and practices. The result of the mentoring is that Bulava Art Studio Children can play dramas.